A construção do conhecimento geométrico à luz da teoria de Van Hiele - Araújo, Andreia Sanches de Oliveira (2015)
This study aims to identify and analyze the construction of geometrical knowledge with the use of different pedagogical activities. The survey was conducted on a group of students of the 2nd year of high school, a public school in the Paraiba do Sul (RJ). The proposal came after a diagnostic evaluation of SAERJINHO, where students did not obtain good assessment, even having studied the entire contents of the textbook. The research features two educational stages, which, when directed, build the geometrical knowledge, causing the student to change the level of geometric thinking. The methodology chosen the Didactic Engineering, which subsidized us theoretical and procedurally. The Educational Product of this research will be a instructional video, containing the topic covered in this study.